IDNLearn.com is your go-to resource for finding expert answers and community support. Get step-by-step guidance for all your technical questions from our knowledgeable community members.
Sagot :
Answer:
v = 6
u = 6×sqrt(2)
Step-by-step explanation:
since the "side angles" are the same, it is an isosceles triangle. that means both sides are equally long.
so, v = 6
for u (the baseline) we use Pythagoras :
c² = a² + b²
u² = 6² + 6² = 36 + 36 = 72
u = sqrt(72) = sqrt(36×2) = 6×sqrt(2)
Answer:
v = 6, u = 6[tex]\sqrt{2}[/tex]
Step-by-step explanation:
This is a 45- 45- 90 triangle with ratio of sides 1 : 1 : [tex]\sqrt{2}[/tex]
That is the legs are equal and the hypotenuse is [tex]\sqrt{2}[/tex] × leg
Then
v = 6 and u = 6[tex]\sqrt{2}[/tex]
We value your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. IDNLearn.com is your go-to source for accurate answers. Thanks for stopping by, and come back for more helpful information.